SUNDANESE PHONOLOGICAL INTERFERENCE INTO ARABIC LANGUAGE IN KETAPANG SOCIETY - Zahra, Dwi Noviatul; Amrulloh, Muhammad Afif; Leviana, Leviana; Febriani, Suci Ramadhanti (Arabi : Journal of Arabic Studies, 2020)
Ketapang is a village in Limau sub-district, Tanggamus district, Lampung province, Indonesia, inhabited by Sundanese speakers. This condition contributes to the variation of Arabic pronunciation, causing irregularities or difficulties known as disturbances. Linguistic phenomenon as a form of language development, something important happens in Arabic. This research was to study phonological interference forms in Sundanese. This research used a qualitative descriptive method with data collection methods through interviews, observations and hearing that comes to the speech of the Ketapang community. The results showed several changes in the phonological change phenomenon, namely phoneme changes and word changes. This study contributes to the knowledge of language development that occurs from phonological disorders in Sundanese to Arabic, thus providing a great deal of knowledge about Arabic linguistic studies.